Selected Topics in Management and Modeling of Complex Systems: Editorial Introduction to Issue 16 of CSIMQ - Peter Forbrig (Complex Systems Informatics and Modeling Quarterly)
The 16th issue of CSIMQ presents four articles that cover a wide range of research topics. The topics of this issue start with psychological aspects of sustainable behavior change within organizations while new technologies are introduced into a company. The range of topics ends with the discussion of specific algorithms that allow entity clustering for Big Data analysis. The goal of these algorithms is the identification of different notations of references that refer to the same real-world object. This entity resolution is also called dedublication. Additionally, an approach for modelling enterprise architecture visualizations is discussed. It is used to specify and develop an architecture cockpit for a company from the financial sector. Within the range of topics is also a paper about the concepts of shared spaces as basis for building business process support systems. In the paper, a generic model is suggested that supports the comparison, analysis, and design of business process support systems.